Limits—Urban Density and Mobility Networks in West Berlin during the Period of Containment - Carlow, Vanessa (Sustainability, 2014)
If space may be conceptualized as a natural resource, much like gas, oil, or minerals, then its production and use can also be thought of as something to be properly managed, taken care of, and not wasted. Limiting the expansion of the footprint of built-up land in urban areas forces this particular resource (space) to be used more efficiently—in a sense, compelling it to be more creative and productive. These spatial constraints on urban areas generate different kinds of densification processes within the existing city, propagating densification, and with it new patterns and uses in urban development, as well as novel approaches to mitigating the hazards of dense urban environments. This paper examines the case of how spatial containment in West Berlin during the period of the Berlin Wall (1961–1989) produced such outcomes. West Berlin during this period can be considered a unique case of spatial containment, where a relatively large and vibrant modern city had to work around a clear and indelible limit to its physical expansion. This paper will discuss ways in which the containment influenced patterns of development in West Berlin toward densification and connectivity, focusing on the expansion of its infrastructural networks, and discuss the development of a new building culture around transformation and densification, including hybrid architectures and mitigation devices to deal with difficult sites produced by the densification.